THE ALCABALA TAX OF DOMAIN TRANSFER DURING THE CONFISCATION IN GUANAJUATO, 1856-1861 (Tzintzun, Revista de Estudios Históricos, 2023)
The article studies the confiscation process in the state of Guanajuato and aimsto demonstrate the problems that occurred in the collection of the domain transfertax, from 1856 to 1861, a period in which the main farms of the entity werealienated. It is shown that the income generated was not as expected by the federalgovernment, due to political problems and the fight between liberals andconservatives, in addition to the resistance of taxpayers to pay the alcabala, eitherfor fear of losing that money or for the inability to pay it due to instability, as wasthe case with tax collection in general.
Keywords: confiscation; taxes; Reform; Guanajuato